Peran Notaris Sebagai Pihak Pelapor dalam Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang - Muhammad Bintang Naufaldy; Gandjar Laksmana Bonaparta (LPPM Universitas Ekasakti Padang, 2023)
Money Laundering (ML) is a significant threat to the economic stability and financial system integrity of a country. To address this issue, the roles of reporting parties such as Notaries, play a crucial role in efforts to prevent and eradicate ML. This research aims to analyze the roles of Notaries in performing their duties as reporting parties in the context of ML prevention and eradication efforts. Additionally, it aims to identify transactions that can be considered suspicious by Notaries in their capacity as reporting parties, such as a lack of training and sufficient understanding of suspicious transaction indicators. Therefore, further efforts are needed to enhance the understanding and training of Notaries. This research employs a normative juridical research method with an approach to various legal regulations governing the roles of Notaries in reporting suspicious transactions related to ML. Data is obtained through the analysis of legal documents encompassing laws, regulations, and guidelines related to the roles of Notaries in preventing and eradicating ML.